Optimization of Agitation Speed and Aeration Rate for Fungal Protein Production from Tofu Whey Using Aspergillus oryzae in a Stirred Tank Bioreactor - Keryanti Keryanti; Rintis Manfaati; Rizky Fauzan; Fauziah Ramadhani; Gustin Mustika Krista; Yohana Fransiska Ferawati; Budi Santoso (Jurnal Teknik Kimia dan Lingkungan, 2026)
Fungal protein, derived from microbial biomass, offers a sustainable protein source and can be produced through fermentation. However, the utilization of tofu whey, an abundant agro-industrial by-product in Indonesia, as a substrate for fungal protein remains underexplored. This study optimizing both agitation speed and aeration rate for Aspergillus oryzae fermentation in a stirred-tank bioreactor. Fermentation was conducted in a 5 L stirred-tank bioreactor with a 3 L working volume for 48 hours at an initial pH of 5 and a temperature of 35℃. Agitation speeds of 150, 200, 250, and 300 rpm were tested at a constant aeration rate of 1.0 vvm to determine the optimum mixing condition. The agitation speed that yielded the highest dry cell weight was then used as the basis for further aeration experiments (0, 0.5, 1.0, and 1.5 vvm). The optimum conditions were obtained at 150 rpm and 1.0 vvm, resulting in a dry cell weight of 7.1 g/L and a protein content of 6.83% (w/w). These findings demonstrate the potential of valorizing tofu whey into fungal protein while highlighting the need for further multi-parameter optimization to enhance protein levels toward single-cell protein standards.